2000
DOI: 10.1164/ajrccm.161.3.9805008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Diaphragmatic Function in Patients with Amyotrophic Lateral Sclerosis

Abstract: In amyotrophic lateral sclerosis (ALS), the progressive loss of upper and lower motor neurons leads to respiratory failure, often with predominant diaphragm dysfunction, and death. Because the diaphragm is the only active inspiratory muscle during rapid eye movement (REM) sleep, there is a high theoretical risk of respiratory disorders during REM sleep in patients with ALS. To assess this hypothesis, we studied sleep characteristics (polysomnography) in 21 patients with ALS, stratified according to the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(137 citation statements)
references
References 36 publications
4
129
0
4
Order By: Relevance
“…23,24 One explanation for this may be accessory muscle atonia, which occurs during REM sleep when the already weak diaphragm is the only functional respiratory muscle and when NIV can best support breathing and improve oxygenation. 25,26 We found that half of our patients were not able to achieve REM sleep. In those who were, NIV had greatest effects on oxygenation in this stage of sleep.…”
mentioning
confidence: 76%
“…23,24 One explanation for this may be accessory muscle atonia, which occurs during REM sleep when the already weak diaphragm is the only functional respiratory muscle and when NIV can best support breathing and improve oxygenation. 25,26 We found that half of our patients were not able to achieve REM sleep. In those who were, NIV had greatest effects on oxygenation in this stage of sleep.…”
mentioning
confidence: 76%
“…[4][5][6][7] In the presence of diaphragmatic dysfunction, REM sleep decreases. 8 Furthermore, sleep disturbances and nocturnal desaturations have been observed in ALS patients with normal respiratory function and preserved diaphragmatic innervation. 9 Although NIV is predominantly used at night, few studies have examined the effect on sleep in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Out of a wide range of tests of respiratory muscle strength, the nonvolitional CMS Pdi,tw had the strongest correlations with indices of sleep-disordered breathing, including significant negative relationships with AHI, hypopnoeas during rapid eye movement (REM) sleep and hypopnoeas during non-REM sleep. ARNULF et al [84] have shown that ALS patients with diaphragmatic dysfunction have reduced time spent in REM sleep, and dramatically shorter median survival times compared with patients without diaphragm dysfunction (217 days versus 619 days). The same group also demonstrated that ALS patients with dyspnoea had significantly lower Pmo,tw following phrenic nerve stimulation than those without dyspnoea (3.71 versus 7.26 cmH 2 O; p=0.001) [85].…”
Section: Neuromuscular Diseasementioning
confidence: 99%